2015
DOI: 10.3846/16486897.2014.998676
|View full text |Cite
|
Sign up to set email alerts
|

Soundscape Design in City Parks: Exploring the Relationships Between Soundscape Composition Parameters and Physical and Psychoacoustic Parameters

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…This phenomenon may be explained by examining the responses of an interview session after the experiment: when people heard birdsong, they described the sound environment with words as "natural" and "pleasant" rather than "loud", suggesting that naturalness and pleasantness may distract people's attention from loudness. Louder birdsong was evaluated to have higher naturalness and pleasantness 50 , which may result in less attention on loudness. Irrespective of masker loudness, Annoyance due to the traffic noise environment increases and Pleasantness decreases sharply when the traffic noise is louder than 47.5 dBA.…”
Section: Ivdiscussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be explained by examining the responses of an interview session after the experiment: when people heard birdsong, they described the sound environment with words as "natural" and "pleasant" rather than "loud", suggesting that naturalness and pleasantness may distract people's attention from loudness. Louder birdsong was evaluated to have higher naturalness and pleasantness 50 , which may result in less attention on loudness. Irrespective of masker loudness, Annoyance due to the traffic noise environment increases and Pleasantness decreases sharply when the traffic noise is louder than 47.5 dBA.…”
Section: Ivdiscussion and Conclusionmentioning
confidence: 99%
“…directions of high frequency sound-birdsong). Single recordings that were played back in the experiment had acceptable realism, which can be validated in the interview after the experiment 50 . To do further study on the examination of influence of spatial information on the masking effects, binaural recording will be considered.…”
mentioning
confidence: 99%
“…This indicates that in addition to the sound level -measured here as LA5 -that also appears in the classification of backgrounded, the temporal variability of the soundmeasured here as L A5 -L A95 -is important for the soundscape to become disruptive. Previous work has suggested the importance of the latter difference or a similar indicator of fluctuation, sometimes referred to as emergence, for predicting the pleasantness of public place soundscapes (Nilsson et al, 2007;Liu and Kang, 2015), as well as for annoyance at home (Bockstael et al, 2011), but never found such strong effects.…”
Section: Disruptive Soundscapesmentioning
confidence: 99%
“…Previous studies have demonstrated that visitors of urban forests in China are mainly young and middle-aged, with 20-35 year olds making up more than 80% of visitors [40,41]. Twelve healthy participants (six female and six male, average 28 ± 3.5 years, five local residents and seven outside residents) with normal hearing, were selected to provide the soundscape information [28,35]. All participants underwent a training process, including being familiarized with all the major sounds and categories in the questionnaire, and performing pilot studies to practice the recording process and learn about the plant communities in the forested area in order to minimize recording bias [42].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, questionnaires (made up of two sections) were used to collect information about perceived occurrences and pleasantness of the soundscape in these urban forests. In the first section, the perceived occurrences of soundscape (POS) included the number of geophony, biophony, and anthrophony sound occurrences that participants recorded in each site [28]. Due to the diurnal variation of biophony in a given habitat, we considered non-mechanical sounds produced by humans to belong to biophony in urban forests because humans' activities are also diurnal variation in the cities [37].…”
Section: Soundscape Informationmentioning
confidence: 99%